Faktor-faktor penyalahgunaan dadah dan penglibatan jenayah dalam kalangan penghuni dan bekas penghuni Pusat Pemulihan Dadah Narkotik (PUSPEN) Bukit Cabang, Perlis - Siti Nurulain, Md. Sobri (2019)
Drug abuse continues to be a problematic social issue in Malaysia. Statistics show an increase in criminal behaviour among drug addicts.Therefore, this study aims to examine the involvement of drug addicts in criminal behaviour. This study focuses on risk factors of criminal behaviour, pattern of crime, types of drug that was taken by the subjects and types of social support as required by the subjects. This study involves nine research subjects comprising clients and former clients of Pusat Pemulihan Dadah Narkotik (PUSPEN), Bukit Cabang, Perlis. Qualitative design through semi structured interview was used for data collection. Thematic analysis was utilized in this study.Results show risk factors of criminal behaviour are environment, peer groups and self-weaknesses. Meanwhile, types of crime are drug trafficking, property crime, inflict an injury, and murder. Among types of drug are heroin, ice, morphine and marijuana. Social support required by the subjects is family and community acceptance to enhance their social functioning.Based on findings of the study, social work intervention through spirituality approach, demographic, social relationship and individual intervention are needed in helping drug addicts to be a productive individual in the society. These actions are significant in reducing the involvement of the drug addicts in criminal behaviour